Electrification Status of Alue Keujrun Village and Kluet River Hydrokinetic Energy Potential: A Survey Report - Muhammad Ikhsan; Nuzuli Fitriadi (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2021)
This paper provides survey results of an electricity system that has been carried out from isolated village of Alue Keujrun, South Aceh, Indonesia. The village has a central photovoltaic power plant and a micro hydro power plant. Various problems in the field such as operation errors, lack of maintenance of the electric power system, low voltage and frequency have been found. Power plant operators have also never received any formal training from any institution. The village is located next to the Kluet river which has a very large potential to become a hydrokinetic power plant energy source. Therefore the Kluet river flow velocity was also measured during the survey and described within this paper. Based on the interviews results with local operators, the village power plant does not have an operating permit. Thus, we consider that it is important to review the types of permits required to establish a power plant in Indonesia, including small-scale power plants.